Genome-wide annotation and expression analysis of WRKY and bHLH transcriptional factor families reveal their involvement under cadmium stress in tomato (Solanum lycopersicum L.) - Khan, Ibrahim; Asaf, Sajjad; Jan, Rahmatullah; Bilal, Saqib; Lubna,; Khan, Abdul Latif; Kim, Kyung-Min; Al-Harrasi, Ahmed (Frontiers in Plant Science, 2023)
The WRKY and bHLH transcription factors have been implicated in the regulation of gene expression during various physiological processes in plants, especially in plant stress responses. However, little information about the heavy metal-responsive SlWRKY and SlbHLH in tomato (Solanum lycopersicum) is available. We performed a genome-wide investigation for these two TF families in S. lycopersicum and determined their role in cadmium (Cd) stress tolerance. Furthermore, ortholog analysis with the Arabidopsis genome led to classifying WRKY and bHLH ortholog genes into nine and 11 clusters, respectively. The comparative phylogenetic analysis revealed duplication events and gene loss in Arabidopsis and S. lycopersicum, which occurred during evolution both before and after the last common ancestor of the two species. Orthologous relationships are also supported by additional evidence, such as gene structure, conserved motif compositions, and protein–protein interaction networks for the majority of genes, suggesting their similar functions. A comprehensive transcriptomics analysis revealed that both WRKY and bHLH genes were differentially expressed in response to cadmium stress as compared with control plants. A gene ontology analysis revealed that most WRKYs and bHLHs are DNA-binding essential proteins that regulate gene expression positively and negatively. Analyses of interaction networks revealed that both WRKYs and bHLHs mediate networks implicated in several stress-signaling pathways. The findings of this work may help us to comprehend the intricate transcriptional control of WRKY and bHLH genes and identify potential stress-responsive genes relevant to tomato genetic improvement. Moreover, identifying heavy metal stress-responsive WRKY and bHLH genes in S. lycopersicum will provide fundamental insights for developing new heavy metal stress-tolerant varieties of tomato crops.